Broad Collaboration to Improve Biological Sciences Students' Writing and Research Skills. - Lisa Brancato; Tina Chan; Anthony Contento (Issues in Science and Technology Librarianship, 2016)
At the State University of New York at Oswego (SUNY Oswego), a faculty member and advisement coordinator, both of the biological sciences department, and the biological sciences librarian have worked together since 2013 to present a workshop called Writing for the Biological Sciences. Offered once per semester, the workshop is sponsored by the Writing Center at SUNY Oswego. The workshop teaches the fundamentals of writing laboratory reports. Primarily geared towards first year biological sciences students, the workshop is open to all students, faculty, and staff. In addition to offering the workshops, one-on-one writing labs were offered starting in spring 2015. The writing labs allow students to meet individually with a biological sciences faculty member to review a draft of the lab report and to gain constructive feedback, as well as for the biological sciences librarian to help students with their research. The writing labs provide personal attention for biological sciences students, faculty, and the librarian to work together to help improve students’ writing and research skills. Advice on offering a writing workshop and writing lab is also discussed. [ABSTRACT FROM AUTHOR]